2006
DOI: 10.1186/1471-2431-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis for treatment of insomnia in school-age children: a retrospective chart review

Abstract: BackgroundThe purposes of this study are to document psychosocial stressors and medical conditions associated with development of insomnia in school-age children and to report use of hypnosis for this condition.MethodsA retrospective chart review was performed for 84 children and adolescents with insomnia, excluding those with central or obstructive sleep apnea. All patients were offered and accepted instruction in self-hypnosis for treatment of insomnia, and for other symptoms if it was felt that these were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Three sessions are conducted for children and three for parents. Components are based on established strategies55–57 and include stimulus control (SC) instructions, sleep hygiene education, and cognitive therapy for children and parents as well as imaginative or hypnotherapeutic and relaxation techniques for children. The children receive a soft toy, the leopard Kalimba, which is employed as a coping model and therapy puppet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three sessions are conducted for children and three for parents. Components are based on established strategies55–57 and include stimulus control (SC) instructions, sleep hygiene education, and cognitive therapy for children and parents as well as imaginative or hypnotherapeutic and relaxation techniques for children. The children receive a soft toy, the leopard Kalimba, which is employed as a coping model and therapy puppet.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to sleep disorders, there have been mostly single case studies or small treatment groups (TGs) and no control group (CG) studies 69–71. Only Anbar and Slothower57 applied hypnosis in a large sample of 84 children with insomnia at the age of 7–17 years and found a significant decrease in symptoms. However, they did not use a CG design.…”
Section: Methodsmentioning
confidence: 99%
“…In the same study, nighttime awakenings were reported to resolve in 52% and improve in 38% of 21 children. 26 Notably, at this Center, instruction in hypnosis was offered to 36% of 6-11-year-old children and 55% of 12-18-year-old children who were newly referred for evaluation of pulmonary symptoms during an 18-month period of study, because it was felt that there was a signifi cant psychological component in their presentation. 9 Thus, hypnosis appears to be applicable to a large number of pediatric patients with respiratory disorders.…”
Section: Hypnosis For Pediatric Respiratory Care 211mentioning
confidence: 99%
“…watching TV). Relaxation therapy such as hypnosis (23), self-hypnosis, autogenous training, and progressive muscle relaxation or biofeedback are also effective in reducing sleep onset latencies and improving sleep quality (24,25). An approach combining these techniques is more effective than simply applying sleep hygiene or cognitive behaviour alone (26,27).…”
mentioning
confidence: 99%